The emotional intelligence for professors of professionals training and education A filed study on a sample of professors from the national institute specialist in professional training for management-Nassef Azzedine- in Blida. - Belhassena , Zoheir; Sadou, Samia (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2021)
The current study aims to explore the level of emotional intelligence among professors of Professional and educational Training and the extent of differences in the emotional intelligence because of the gender variable and seniority. The sample consisted of 30 professors 13 of them are females who were randomly selected from a community of 52 professors from The National Institute for Professional Training in Management (Nassef Azzedine) in Blida. To achieve the study, the objectives’ The descriptive method was used and the Farouk El-Sayed Mohamed and Abdel-Sami Abdu scale’s 2006 which Consists of 58 items divided into five dimensions, namely (Emotional awareness, emotions management, Emotions regulation, Empathy, Social communication skill) And regulated according to the Algerian environment by the researcher (Fatima Ghalem 2015) as a tool for measuring emotional intelligence, and as tools for statistical analysis. We used the test (T) for one sample, to determine the level of emotional intelligence by comparing calculated averages with the theoretical averages of the scale, And (T) test for two independent samples to calculate the differences for gender and to analyze the mono-variance for calculating the differences for seniority using the statistical package for social sciences (SPSS).Thus, the results indicated the rise of emotional intelligence level among professors and the absence of statistically significant differences due to seniority and the absence of differences due to gender variable except in the emotional subconscious dimension and organize emotions in favor of females.